The Effect of Nasal Patency and Anatomy During Asymmetrical Nasal High Flow - Barnes M (American Physiological Society, 2026)
Nasal high flow (NHF) with the asymmetrical cannula interface (AI) is increasingly used as respiratory support across a broad range of patients. By incorporating one unilaterally oversized prong, the AI enhances dead-space clearance and increases airway pressure. This study investigated the effects of nasal patency and anatomical variability of the upper airways during NHF delivered with the AI. Twenty healthy adults underwent three 3-hour study periods whereby heated, humidified air was delivered at 30L/min via either an AI, a symmetrical interface (SI), or a control condition without NHF. Nasal patency was assessed every 30 minutes using acoustic rhinometry, rhinomanometry and a self-assessment questionnaire. Measurements were quantified using a laterality index, and ventilation was monitored by respiratory inductance plethysmography. Nasal anatomy was evaluated using magnetic resonance imaging, and airway replicas reconstructed from these images, including original and mirrored models, were tested in bench-top experiments. All measures of nasal patency were significantly positively correlated (p < 0.001). There was no association between the AI laterality index and respiratory rate or tidal volume. In the 3D models, both airway pressure and dead-space clearance increased when the leak area was reduced by changing the SI to the AI. Compared to the originals, mirroring the nasal passages showed no difference except for the model with severe nasal septum deviation. NHF with SI or AI did not alter dominant side of nasal patency, which did not affect ventilation. Nares morphology, rather than physiological alternation in nasal patency, may have greater influence on pressure generation during NHF.